Analisis Keadilan Substantif dalam Putusan Kasasi Terkait Tindak Pidana Kehutanan - Desi Optapia; Dona Raisa Monica; Fristia Berdian Tamza (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Forests play an important role in supporting the lives of Indonesian and even international communities. However, the problem of forestry crimes today is a fairly complicated problem to overcome. This is due to, among other things, the lack of regional boundaries, low intensity and effectiveness of patrol/supervision, very limited and unprofessional forest security personnel and facilities, weak coordination among law enforcement officers, weak law enforcement against violators and the lack of perception from community members themselves of the importance of forest resources for all mankind. Supreme Court Decision Number 121 K/PID.SUS-LH/2024 is the focus of this study, because it highlights the challenges and complexities in law enforcement against perpetrators of forestry crimes. In this regard, there are problems related to legal uncertainty, differences in legal interpretation, and the complexity of cases that influence judges' decisions at the cassation level. The problem in this study is how is the basis for the judge's considerations in sentencing perpetrators of forestry crimes and whether the decisions given are in accordance with the principles of substantive justice. This research method is carried out using a normative juridical approach and an empirical juridical approach. The data used are primary data and secondary data. The data collection procedure in writing this research is by means of literature and field studies. Data analysis uses qualitative analysis.